Cell‐specific CO2 fixation rates of two distinct groups of plastidic protists in the Atlantic Ocean remain unchanged after nutrient addition. Issue 2 (23rd January 2015) - Grob, Carolina; Jardillier, Ludwig; Hartmann, Manuela; Ostrowski, Martin; Zubkov, Mikhail V.; Scanlan, David J.
Summary To assess the role of open‐ocean ecosystems in global CO2 fixation, we investigated how picophytoplankton, which dominate primary production, responded to episodic increases in nutrient availability. Previous experiments have shown nitrogen alone, or in combination with phosphorus or iron, to be the proximate limiting nutrient(s) for total phytoplankton grown over several days. Much less is known about how nutrient upshift affects picophytoplankton CO2 fixation over the duration of the light period. To address this issue, we performed a series of small volume (8–60 ml) – short term (10–11 h) nutrient addition experiments in different regions of the Atlantic Ocean using NH4Cl, FeCl3, K medium, dust and nutrient‐rich water from 300 m depth. We found no significant nutrient stimulation of group‐specific CO2 fixation rates of two taxonomically and size‐distinct groups of plastidic protists. The above was true regardless of the region sampled or nutrient added, suggesting that this is a generic phenomenon. Our findings show that at least in the short term (i.e. daylight period), nutrient availability does not limit CO2 fixation by the smallest plastidic protists, while their taxonomic composition does not determine their response to nutrient addition.